Norm of Bethe vectors in models with gl(m|n) symmetry - A. Hutsalyuk; A. Liashyk; S.Z. Pakuliak; E. Ragoucy; N.A. Slavnov (Nuclear Physics B, 2018)
We study quantum integrable models solvable by the nested algebraic Bethe ansatz and possessing gl(m|n)-invariant R-matrix. We compute the norm of the Hamiltonian eigenstates. Using the notion of a generalized model we show that the square of the norm obeys a number of properties that uniquely fix it. We also show that a Jacobian of the system of Bethe equations obeys the same properties. In this way we prove a generalized Gaudin hypothesis for the norm of the Hamiltonian eigenstates.